DOES HEALTH AND EDUCATION AFFECT REGIONAL INEQUALITY IN WEST JAVA - Rahim, Dian Anggraeny; Citarayani, Irma (Fakultas Teknik Universitas Krisnadwipayana, 2023)
Sustainable development not only aims to increase people's incomes but also to improve people's welfare and reduce regional inequality. To realize this, the West Java regional government has several policies, including improving education and providing easy access to health care for the community. This study aims to determine the influence of these two variables on regional inequality, with GDP per capita as a moderation variable. Using the SEM-PLS analysis tool and data for 2015–2023, the results of this study show that education and health directly or indirectly have a positive influence on GDP per capita. For regional inequality, both variables have a negative influence.